The UV-B Photoreceptor UVR8: From Structure to Physiology - Jenkins, Gareth I. (American Society of Plant Biologists, 2014)
Low doses of UV-B light (280 to 315 nm) elicit photomorphogenic responses in plants that modify biochemical composition, photosynthetic competence, morphogenesis, and defense. UV RESISTANCE LOCUS8 (UVR8) mediates photomorphogenic responses to UV-B by regulating transcription of a set of target genes. UVR8 differs from other known photoreceptors in that it uses specific Trp amino acids instead of a prosthetic chromophore for light absorption during UV-B photoreception. Absorption of UV-B dissociates the UVR8 dimer into monomers, initiating signal transduction through interaction with CONSTITUTIVELY PHOTOMORPHOGENIC1. However, much remains to be learned about the physiological role of UVR8 and its interaction with other signaling pathways, the molecular mechanism of UVR8 photoreception, how the UVR8 protein initiates signaling, how it is regulated, and how UVR8 regulates transcription of its target genes.